2021
DOI: 10.1039/d0na00966k
|View full text |Cite
|
Sign up to set email alerts
|

Advanced analysis of magnetic nanoflower measurements to leverage their use in biomedicine

Abstract: Magnetic nanoparticles are an important asset in many biomedical applications ranging from the local heating of tumours to targeted drug delivery towards diseased sites. Recently, magnetic nanoflowers showed a remarkable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…), which all affect the heating efficiency of MNPs in MHT, 142 it is also important to consider the behavior of MNPs not as individual units but as a whole sample because certain inter-particle interactions between MNPs can have a significant effect on MHT heat performances. 178,179 In fact, it has been observed that the SAR properties of MNPs profoundly varies either positive or negative based on the inter-particle interactions thus on the orientation of their collective magnetic easy axis, occurring for instance under certain nanoparticle concentration ranges and applied magnetic field conditions. 6, 10, 16, 84, 167, 180-183 Salas, G. et al investigated the heating abilities of 22 nm MNPs in agarose at two different nanoparticle concentrations (2.5 mg Fe and 10 mg Fe /mL) and noted a higher reduction of SAR at high concentrations with respect to the less concentrated samples.…”
Section: Magnetic Assemblies and Correlation With Mht Heat Performancesmentioning
confidence: 99%
“…), which all affect the heating efficiency of MNPs in MHT, 142 it is also important to consider the behavior of MNPs not as individual units but as a whole sample because certain inter-particle interactions between MNPs can have a significant effect on MHT heat performances. 178,179 In fact, it has been observed that the SAR properties of MNPs profoundly varies either positive or negative based on the inter-particle interactions thus on the orientation of their collective magnetic easy axis, occurring for instance under certain nanoparticle concentration ranges and applied magnetic field conditions. 6, 10, 16, 84, 167, 180-183 Salas, G. et al investigated the heating abilities of 22 nm MNPs in agarose at two different nanoparticle concentrations (2.5 mg Fe and 10 mg Fe /mL) and noted a higher reduction of SAR at high concentrations with respect to the less concentrated samples.…”
Section: Magnetic Assemblies and Correlation With Mht Heat Performancesmentioning
confidence: 99%
“…by Bender et al (2019Bender et al ( , 2021. Regarding an automated data analysis, the KA in particular has great potential as also discussed in the context of other measurement techniques (Karpavic ˇius et al, 2021). This approach could also be applied when simultaneously analyzing data sets of complementary characterization techniques.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…94 The collective characteristics of the interacting crystallites permit a large magnetic moment while retaining the faster dynamics typically associated with smaller particles. 95…”
Section: Synthesis Proceduresmentioning
confidence: 99%
“…94 The collective characteristics of the interacting crystallites permit a large magnetic moment while retaining the faster dynamics typically associated with smaller particles. 95 The chemical coprecipitation and thermal decomposition synthesis are the most relevant and efficient methods for preparing MNPs for ferrofluids. The same conclusion was reached in a most recent review on SPION synthesis for magnetic particle imaging.…”
Section: Synthesis Of Magnetic Nanoparticles For Ferrofluidsmentioning
confidence: 99%